AB1226-HPR Psychological and Behavioral Reactions When Patients with Rheumatoid Arthritis Start Biological Dmards. (9th June 2015) - Motonaga, T.; Mori, M.; Mabuchi, M.; Sakai, Y.; Iijima, Y.; Hidaka, T.; Kameda, H.; Kawahito, Y.
Abstract : Background: Patients with rheumatoid arthritis (RA) must often deal with a multitude of sometimes contradictory thoughts and feelings when doctors introduce the use of biological disease-modifying anti-rheumatic drugs (DMARDs) for the treatment of active RA. As these emotional responses can positively or negatively influence a patient's attitude toward such medication, we argue that medical staff should consider the psychological processes of patients who are making decisions regarding treatment using biological DMARDs. Objectives: This study aimed to qualitatively examine the psychological and behavioral reactions of patients with RA to the commencement of biological DMARDs. Methods: Twenty patients (mean age: 56.5±10.8 years) were recruited between February and August 2011 from a patient group and from four medical institutions. Sixteen of the 20 patients were treated with biological DMARDs. We interviewed the patients using a semi-structured protocol, asking them about their thoughts, feelings, and opinions regarding biological therapy. We also conducted a qualitative content analysis to discover codes and categories about psychological and behavioral reactions to biological DMARDs. Results: Common patient feelings included worry and anxiety toward the use of these drugs. This is because the proposed introduction of "serious" biological treatment made patients see their conditions in a more negative light. However, patients sometimes exhibited positive reactions to DMARDs as they were hopeful that biological treatment could reduce their pain and improve their quality of life. Thus, they experienced both positive and negative feelings. The patients experienced fluctuations of anxiety regarding the use of these drugs over time, and these fluctuations influenced their attitudes toward treatment more generally. Their anxiety increased at first, caused by worry about pain, but after some coping exercises, these negative feelings were temporarily alleviated. Their trust in the doctor tended to reduce anxiety, whereas their negative impression to the doctor lead to their increased anxiety for using the drugs. Conclusions: Trustful mutual relationships between patients and physicians might be an important factor when helping patients cope with fluctuations in anxiety for the use of biological DMARDs, and it is possible that such relationships can help lead to adequate treatment. Disclosure of Interest: None declared